Factors predicting one or two sentinel lymph nodes to be accepted for sentinel lymph node biopsy alone after neoadjuvant therapy in initially node-positive breast cancer patients. (December 2021) - Tsai, Li-Wei; Lee, Yi-Hsuan; Lo, Chiao; Lien, Huang-Chun; Wang, Ming-Yang; Jan, I-Shiow; Yen, Ruoh-Fang; Hu, Fu-Chang; Huang, Chiun-Sheng
Abstract: Background: Current guidelines recommend harvesting ≥3 sentinel nodes if sentinel lymph node biopsy (SLNB) alone is considered after neoadjuvant therapy (NAT) for initially node-positive (cN+) breast cancer. We attempted to investigate factors predicting one or two sentinel lymph nodes harvested to be accepted for SLNB alone after NAT in initially cN + patients. Methods: Overall, 157 patients who received NAT (clinically T1–3/N1–2/M0) and underwent SLNB were identified from a prospectively maintained database. Significant factors were identified using a multiple logistic regression model. Results: The overall SLN identification rate was 83.4%. Failed SLN identification was associated with a 2-day protocol using a single tracer (odds ratio: 0.331 [95% confidence interval CI: 0.132–0.830], p = 0.018), age >52 years (0.345 [0.131–0.913], p = 0.032), and lobular histology (0.156 [0.026–0.944], p = 0.043). The overall false-negative SLNB rate was 14.7%. Its increased risk was associated with radioactivity count >530 for any SLN during SLNB (96.4 [4.00–2320], p = 0.005), age ≥57 years (34.2 [1.92–610], p = 0.016), and taxane use (105 [1.02–10700], p = 0.049); its decreased risk was associated with more harvested SLNs (0.191 [0.054–0.669], p = 0.01) and dual tracers (0.101 [0.012–0.843], p = 0.034). A predictive model using these factors achieved an area under the curve of 0.935 (95% CI: 0.878–0.991). Conclusion: When taxane was administered during NAT, the false-negative rate was predicted at <5% for patients aged <57 years, if 1–2 SLNs were harvested using dual tracers, and when the count of every SLN was lower than 530 after NAT in cN + breast cancer. Highlights: One/two SLNs harvested via dual tracers can be considered for SLNB alone after NAT. Increased risk of false-negative SLNB correlated with radioactivity count >530. Increased risk of false-negative SLNB correlated with age ≥57 years and taxane use. Decreased risk correlated with more harvested SLNs and dual tracers. A predictive model using the above factors achieved an AUC of 0.935